2021
DOI: 10.1111/dth.14826
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world drug survival and reasons for treatment discontinuation of biologics and apremilast in patients with psoriasis in an academic center

Abstract: The use of systemic agents is considered standard of care in patients with moderate to severe psoriasis, and these therapeutic agents are marked by a favorable risk-benefit profile, however, are plagued by high attrition. One questionnaire-based survey of 692 patients who had previously taken a biologic agent found that patients discontinued their medications after 11 to 20.5 months. 1 Our study aims to present additional real-world clinical data regarding the reasons behind discontinuation of these novel agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
2
4
1
Order By: Relevance
“…Therefore, these are complex patients with treatment‐resistant disease. Data obtained by our drug survival analysis are consistent with those obtained in other studies, which also found no differences in the duration of treatment depending on the characteristics of the patients, including previous biological treatment 6,7,13,14 . However, in our study CKD was associated with shorter treatment duration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, these are complex patients with treatment‐resistant disease. Data obtained by our drug survival analysis are consistent with those obtained in other studies, which also found no differences in the duration of treatment depending on the characteristics of the patients, including previous biological treatment 6,7,13,14 . However, in our study CKD was associated with shorter treatment duration.…”
Section: Discussionsupporting
confidence: 91%
“…Data obtained by our drug survival analysis are consistent with those obtained in other studies, which also found no differences in the duration of treatment depending on the characteristics of the patients, including previous biological treatment. 6,7,13,14 However, in our study CKD was associated with shorter treatment duration. To our knowledge, no other studies have described apremilast survival depending on the presence of CKD.…”
Section: T a B L E 1 Patient Baseline Demographics And Clinical Chara...contrasting
confidence: 58%
“…In a cohort of patients with palmoplantar pustulosis, however, apremilast was associated with the longest survival (65 weeks) comparing to classic systemic treatments, such as cyclosporine, acitretin plus PUVA, methotrexate, acitretin, alitretinoin and fumaric acid esters [13]. Primary treatment failure was the most common reason for apremilast discontinuation in a USA study comparing various biologics and apremilast as well as in a smaller Austrian study [5,10]. Loss of efficacy was the main reason for apremilast cessation in a Japanese study (46.4%) [9].…”
Section: Take-home Messagementioning
confidence: 97%
“…Psoriasis treatment with biologics and small-molecule agents is of finite duration, most often due to efficacy-related reasons [3] The probability that psoriasis patients will stay on a biologic treatment for ≥3 years is 53%-58% [4]. Anti-drug antibodies, genomic and transcriptomic parameters as well as non-compliance could possibly explain this phenomenon [4,5]. Forty-five of 382 (11.78%) ESTEEM 2 participants, who received apremilast, discontinued treatment due to lack of efficacy by week 52 [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is especially useful for patients in whom the use of biologic drugs it to be avoided (e.g., those with cancer, latent tuberculosis infection, or infective hepatitis). However, little is known about the drug survival associated with apremilast, in the real world, especially in the long term 2–19 . Moreover, there is also a variability in the term survival of Apremilast (APR) and its predictive factors for the treatment of psoriasis.…”
Section: Introductionmentioning
confidence: 99%